Participatory research in the selection and evaluation of improved groundnut varieties in Mali - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
New groundnut varieties are empowering women farmers in Mali after a 3-year long participatory research in the selection and evaluation of improved groundnut varieties has yielded positive results. Women groundnut farmers in the village of Wakoro have selected the varieties ICGV86124, Fleur 11 and JL 24, which produce high-quality seed. The women are organized into a groundnut farmers’ association and have taken up groundnut growing as a business.